MULTIPLEX SYBR GREEN ASSAY FOR CORONAVIRUS DETECTION USING FAST REAL-TIME RT-PCR - & et al., Salah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to provide a local database for detection of coronavirus (CoV) species in suspect individual with respiratory tract infections like influenza type A and a tuberculosis using multiplex Sybr green reverse transcriptase real-time PCR (rRT-PCR) technique. A total of 500 samples was collected from individuals suffering from upper and/or lower respiratory tract diseases for testing of 4 CoV species (229E, OC43, NL63, and HKU1). RNA extracted, amplified and subsequent the positive samples sequencing. The results showed melting curve analysis (Tm) of the specific amplicons (79.73±0.36) and 9% positive for CoVs and some of them have other co-infection such as influenza virus 26.67%, and TB 11.11%. On the other hands, the CoVs were detected 4.62% in upper respiratory samples and 20.39% with lower respiratory samples. Sequencing results pointed out two isolates were CoV-NL63 and four isolates were CoV-229E, with first record accession number MN086823.1 and MN086824.1, respectively in GenBank. In conclusion, this rRT-PCR showed the rapid and efficient detection of CoVs with few copies number. This allows being used for the diagnosis of CoVs along with other respiratory viruses in a multiplex assay to reduce processing time. Subsequent applied nested RT-PCR to overcome the low viral load.